2021
DOI: 10.1007/s12598-020-01669-x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-core–shell-structured LiFePO4@Na3V2(PO4)3@C composite for enhanced low-temperature performance of lithium-ion batteries

Abstract: In this work, a multi-core-shell structured LiFePO4@Na3V2(PO4)3@C (LFP@NVP@C) composite is successfully designed and prepared to address inferior lowtemperature performance of LiFePO4 cathode for lithium ion batteries. TEM confirms the inner NVP and outer carbon layers co-existed on the surface of LFP particle. When evaluated at low-temperature operation, LFP@NVP@C composite exhibits an evidently enhanced electrochemical performance in term of higher capacity and lower polarization, compared with LFP@C. Even a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 38 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Therefore, the rst choice of lithium iron phosphate cathode material was more suitable for storing lithium ions. In previous studies on lithium-ion battery half-cells, the platform voltages of lithium in sodium vanadium phosphate and lithium iron phosphate were approximately 3.6 V and 3.4 V, respectively, with a difference of 0.2 V 29,30,31 . When we replaced the lithium metal in this battery system with an aluminum negative electrode, the standard hydrogen electrode potential of aluminum and lithium were − 1.66 and − 3.04 V vs SHE, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, the rst choice of lithium iron phosphate cathode material was more suitable for storing lithium ions. In previous studies on lithium-ion battery half-cells, the platform voltages of lithium in sodium vanadium phosphate and lithium iron phosphate were approximately 3.6 V and 3.4 V, respectively, with a difference of 0.2 V 29,30,31 . When we replaced the lithium metal in this battery system with an aluminum negative electrode, the standard hydrogen electrode potential of aluminum and lithium were − 1.66 and − 3.04 V vs SHE, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…However, it can be seen from Figure h,i that the improvement in the low-temperature performance of cells is still relatively limited. In addition, comparison of the low-temperature performance of LFMP with some similar materials described in the literature is listed in Table It can be found that the low-temperature performance of the prepared LFMP@B/P–C material is poorer than other similar materials, thereby it needs to further improve the low-temperature performance of LFMP in the future. Furthermore, the too low temperature could cause the solidification of solvents such as ethylene carbonate in the electrolyte, which hinders the diffusion of lithium ions and increases the impedance of the cells.…”
Section: Resultsmentioning
confidence: 99%
“…Nonaqueous lithium‐ion batteries (LIBs) have been dominating the portable electronics and electric/hybrid vehicles market due to their high energy density and long cycle life, [ 1–5 ] but the limitation of lithium resources, high‐cost, and safety issue, [ 3,4,6–10 ] hinder their further development for larger‐scale energy storage applications. Nonaqueous sodium‐ion batteries (SIBs) and potassium‐ion batteries (KIBs) use relatively abundant and low‐cost sodium and potassium elements, have become alternatives to LIBs.…”
Section: Introductionmentioning
confidence: 99%